Research of modern brushless DC motors to use them in the system of control and stabilization of millimeter-wave antenna - N. M. Naumovich; O. S. Maltsev; S. P. Urbanovich; M. V. Davydov; R. A. Bogdanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of the reserch of possibilities of using brushless motors in the stabilization systems of scanning antennas onboard millimeter wave radar are given. For this purpose, peculiarities of change of momentary motor shaft speed for various values of acceleration have been studied in the course of experimental studies, as well as a comparison of the possible operating modes have been complited. The reserch was carried out with engines MAXON EC-max-2 .